Optimizing Local Control in High‐Grade Uterine Sarcoma: Adjuvant Vaginal Vault Brachytherapy as Part of a Multimodal Treatment. (18th September 2017) - Annede, Pierre; Gouy, Sébastien; Mazeron, Renaud; Bentivegna, Enrica; Maroun, Pierre; Petit, Claire; Dumas, Isabelle; Leary, Alexandra; Genestie, Catherine; Lhommé, Catherine; Deutsch, Eric; Morice, Philippe; et al.
Abstract : Purpose: The phase III European Organization for Research and Treatment of Cancer 55874 study has shown that external beam radiotherapy (EBRT) given as adjuvant treatment decreased locoregional recurrences from 40% to 20% in patients (pts) with localized uterine sarcomas (US). No data exist, however, on the place of brachytherapy (BT). Material and Methods: We conducted a single‐center retrospective analysis of pts receiving adjuvant BT of the vaginal vault based on the vaginal mold technique as part of their multimodal adjuvant treatment for a high‐grade US from 1985 to 2015. Treatment characteristics, patterns of relapse, and toxicity were examined. Results: Median follow‐up time was 5.5 years. A total of 98 pts with high‐grade US were identified: 81 leiomyosarcomas and 17 undifferentiated sarcomas. Postoperative chemotherapy was delivered in 53 pts. Median dose of EBRT was 45 Gy in 25 fractions. High‐dose rate, low‐dose rate, and pulsed‐dose rate techniques were used in 66, 31, and 1 pts, respectively. At last follow‐up, six pts (6.1%) experienced a locoregional relapse as first event. The International Federation of Gynecology and Obstetrics stage and the tumor size were associated with a higher probability of local relapse. When focusing on pts with stage I‐III disease, 5‐year overall survival was 77% (95% confidence interval: 67%–87%) and 5‐year survival without locoregional failure was 91% (83%–98%). Toxicities were mild to moderate, with only four acute grade 3 toxicities and two grade 3 late effects. Conclusion: Vaginal vault BT as part of a multimodal adjuvant treatment was associated with a high locoregional control rate and with acceptable side effects in localized high‐grade US. Abstract : This study reports on an experience with adjuvant treatments in localized high‐grade uterine sarcomas, rare tumors accounting for 1%‐2% of all uterine cancers. The local efficacy and toxicity of a multimodal adjuvant strategy including brachytherapy of the vaginal vault were examined.